2019
DOI: 10.1002/hed.25905
|View full text |Cite
|
Sign up to set email alerts
|

Significance and management of incidentally diagnosed metastatic papillary thyroid carcinoma in cervical lymph nodes in neck dissection specimens

Abstract: Background The management of patients with incidentally discovered metastatic thyroid cancer in cervical lymph nodes in neck dissection specimens for other pathologies is unclear. Methods Retrospective review of neck dissection specimens for nonthyroid malignancy during a 30‐year period was undertaken to identify incidental metastatic papillary thyroid cancer (PTC). Results Twenty‐six patients had an incidental finding of PTC in lymph node(s) in neck dissection specimens. Subsequent ultrasound of the thyroid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A small case series (26 patients, all adults) was found that showed no difference in outcome (i.e. disease-free at median follow-up of 4 years) in patients who underwent total thyroidectomy vs active surveillance ( 91 ). Similar to the 2015 ATA Pediatric Guideline, the expert panel recommends extensive neck US in these cases to detect contralateral disease/regional lymph node spread ( 8 ).…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 96%
“…A small case series (26 patients, all adults) was found that showed no difference in outcome (i.e. disease-free at median follow-up of 4 years) in patients who underwent total thyroidectomy vs active surveillance ( 91 ). Similar to the 2015 ATA Pediatric Guideline, the expert panel recommends extensive neck US in these cases to detect contralateral disease/regional lymph node spread ( 8 ).…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 96%
“…in both the management and the diagnosis of malignancy of unsuspected thyroid tissue in cervical lymph nodes. [3][4][5] Some authors argue that any and all thyroid tissues in cervical lymph nodes represent metastatic thyroid carcinoma, 6 citing that metastases of PTC can have variable papillary and/or follicular architecture, that the follicular elements can resemble normal thyroid follicles, and that some metastases may completely lack papillary architecture. These authors argue that a primary thyroid tumor always exists, even though it may not be palpable, found on imaging, or visualized on routine or thin pathologic sectioning.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest discussion in relation to elective dissection or not of the recurrent chain is based on its morbidity, especially with regard to definitive postoperative hypoparathyroidism (Mallick & Harmer, 2018). According to Yan et al, (2021), Luster et al, (2019) and Mandapathil et al, (2019), recurrent neck dissection is associated with a higher incidence of postoperative hypoparathyroidism, ranging from 14.0% to 54.6% (transient) and from 4.0% to 17 .4% (definite), and also the higher incidence of inadvertent parathyroid resection (Luster, Duntas, & Wartofsky, 2019;Mandapathil, Lennon, Ganly, Patel, & Shah, 2019;Yan, Xiang, Wang, & Wang, 2021). Chang et al, (2020), Godlewska et al, (2020) and Terris & Duke, (2016), in which 4.0% of the patients developed definitive hypoparathyroidism, suggest that recurrent dissection is not routinely performed in all cases of PC, but only in those with clinically detectable metastases or in patients at higher risk Godlewska et al, 2020;Terris & Duke, 2016).…”
Section: Neck Dissectionmentioning
confidence: 99%